A new subspecies of Glabroculus elvira (Eversmann, 1854) (Lepidoptera, Lycaenidae) from the Dzhungarian Gobi desert, Mongolia - Churkin, Sergei V.; Kolesnichenko, Kirill A. (Zootaxa, 2019)
Glabroculus elvira suadela ssp. n. is described from the Dzhungarian Gobi desert. The species was not previously recorded in Mongolia. The new subspecies can be easily differentiated from other known conspecific taxa by the bright shiny upperside in males and contrasting upperside in females, with conspicuous whitish spots.